Virosome engineering of colloidal particles and surfaces: bioinspired fusion to supported lipid layers. Issue 15 (23rd March 2016) - Fleddermann, J.; Diamanti, E.; Azinas, S.; Košutić, M.; Dähne, L.; Estrela-Lopis, I.; Amacker, M.; Donath, E.; Moya, S. E.
Abstract : Inmunostimulating reconstituted influenza virosomes (IRIVs), liposomes with functional viral envelop glycoproteins, fuse on supported lipid bilayers with a pH dependent mechanism, in analogy to the virus fusion on cell membranes. Abstract : Immunostimulating reconstituted influenza virosomes (IRIVs) are liposomes with functional viral envelope glycoproteins: influenza virus hemagglutinin (HA) and neuraminidase intercalated in the phospholipid bilayer. Here we address the fusion of IRIVs to artificial supported lipid membranes assembled on polyelectrolyte multilayers on both colloidal particles and planar substrates. The R18 assay is used to prove the IRIV fusion in dependence of pH, temperature and HA concentration. IRIVs display a pH-dependent fusion mechanism, fusing at low pH in analogy to the influenza virus. The pH dependence is confirmed by the Quartz Crystal Microbalance technique. Atomic Force Microscopy imaging shows that at low pH virosomes are integrated in the supported membrane displaying flattened features and a reduced vertical thickness. Virosome fusion offers a new strategy for transferring biological functions on artificial supported membranes with potential applications in targeted delivery and sensing.